2013
DOI: 10.1073/pnas.1320041110
|View full text |Cite
|
Sign up to set email alerts
|

Cross-neutralizing human anti-poliovirus antibodies bind the recognition site for cellular receptor

Abstract: Most structural information about poliovirus interaction with neutralizing antibodies was obtained in the 1980s in studies of mouse monoclonal antibodies. Recently we have isolated a number of human/chimpanzee anti-poliovirus antibodies and demonstrated that one of them, MAb A12, could neutralize polioviruses of both serotypes 1 and 2. This communication presents data on isolation of an additional cross-neutralizing antibody (F12) and identification of a previously unknown epitope on the surface of poliovirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 27 publications
2
46
0
1
Order By: Relevance
“…It is interesting that when primate antibodies were identified that cross-neutralize both poliovirus serotypes 1 and 2 (thereby avoiding the usual highly exposed antigenic sites), the antibody binding sites overlapped that of the receptor, and the escape substitutions included residues 65, 109, and 166 of VP1 (37,38). These findings clearly are very similar to our results using neutralizing VHHs and suggest that the mechanisms of neutralization are similar.…”
Section: Discussionsupporting
confidence: 81%
“…It is interesting that when primate antibodies were identified that cross-neutralize both poliovirus serotypes 1 and 2 (thereby avoiding the usual highly exposed antigenic sites), the antibody binding sites overlapped that of the receptor, and the escape substitutions included residues 65, 109, and 166 of VP1 (37,38). These findings clearly are very similar to our results using neutralizing VHHs and suggest that the mechanisms of neutralization are similar.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, neutralizing RBS-targeting antibodies of differing germline origins have been observed in other viruses, including influenza virus, HIV, and poliovirus (32)(33)(34). In the case of influenza virus, it has been possible to recognize a signature binding motif on the CDR H3 loop (33).…”
Section: Resultsmentioning
confidence: 89%
“…However, for nonenveloped viruses, neutralizing MAbs usually target one particular step of entry (41,44). For example, MAbs against enteroviruses mostly inhibited the attachment step (41,45,46), whereas a few antibodies which target the internal epitopes within VP1 or VP4 were suggested to exhibit neutralization only at the postattachment stage by inhibiting conformation transitions (47)(48)(49). Interestingly, in the present study we found that a group of anti-EV71 MAbs (represented by D5) exhibited neutralization at both the pre-and postattachment stages in a cell type-independent manner.…”
Section: Discussionmentioning
confidence: 99%